The Regiospecific Preparation of 2-Substituted Tribenzotriquinacenes - Saravanakumar, Rajendran; Markopoulos, Georgios; Bahrin, Lucian Gabriel; Jones, Peter G.; Hopf, Henning (Synlett, 2013)
Several substituted tribenzotriquinacene derivatives (TBTQ) carrying functional groups exclusively in the 2-position (OMe, OH, Br, CHO, CN, styryl, etc.) have been prepared by our new synthesis of the tribenzotriquinacene framework. The route has been extended to the preparation of a double-cup molecule in which two TBTQ moieties are fused by a benzene ring. The trans configuration of one of the diastereomers of this hydrocarbon was established by X-ray structural analysis.
Keywords: cuplike aromatics; Friedel–Crafts cyclizations; cycloeliminations; convex molecules; chiral aromatics; double-cup structures; single-crystal X-ray structural analysis